Методика квантитативной типологии текста: учебное пособие / П. М. Алексеев - Алексеев Павел Михайлович (ЛГПИ, 1983)
Экземпляры: КХ (20120315) / Инвентарный номер: 0263842 / Цена: 0.14 / Сис.шифр: 81 / Авт.знак: А 47 / ГРНТИ: 16 / ББК: 81.1